The challenges of 3D food printing in Malaysian Manufacturing Firms: a preliminary study - Lee, Te Chuan; Zaidi, Nabiha Husna (2023)
Additive manufacturing (AM) or 3D printing creates three-dimensional objects by adding materials using digital format files to achieve the desired shape. Researchers worldwide, including those in Malaysia, have shown interest in AM for over a decade. Although 3D printing has gained widespread adoption, 3D food printing is still in its early stages. This study aims to explore the challenges of implementing 3D printing technology in Malaysian food manufacturing firms. The research utilized a semi-structured interview method, conducting in-depth interviews with seven respondents. Snowball sampling was employed to identify potential experts, building upon the recommendations of the initial respondent. The literature review identified nine challenges: timeconsuming processes, lack of standardization, scarcity of expertise, extrusion molds and materials, limitations in scalability, cost, food safety, halal compliance, and intellectual property. During the interviews, many respondents revealed that they had not yet integrated 3D food printing into their operations. Furthermore, respondents introduced a new challenge, which was related to spare parts and maintenance. In conclusion, the investigation revealed that the implementation of 3D food printing in Malaysian manufacturing firms is still at an early stage, as evidenced by the challenges reported by the respondents